Role of Endothelial Dysfunction Marker along with Toll-like Receptors 4 (TLR-4) Polymorphism in Patients with Type 1 Diabetes Mellitus - Alkinani, Ibrahim Abd Ali Abdul Sada; Al-Hamadani, Adnan Hamad Aubaid (Medical Science Journal for Advance Research, 2025)
Background: The immune system specifically destroys insulin-producing beta cells in the pancreas in type 1 diabetes mellitus (T1DM), an autoimmune disease. CD4+T cells plan the attack, while CD8+T cells kill the beta cells directly, causing insulin insufficiency and uncontrolled blood sugar levels. Objective: The aim of study is to evaluate E-selectin as a diagnostic biomarker for T1D patients. Additionally, evaluate of TLR-4 polymorphisms by PCR-RFLP. Methodology: Overall, 150 participants were included (75 patients and 75 healthy control) the ages between (10 and 35) years.The serum levels of E-selectin were estimated by ELISA kits. Results: The present study demonstrates that the level of E-selectin was significantly higher in T1D patients compared with controls. As regards the (TLR4) Asp299Gly (rs4986790) genes in patients with polymorphism, In T1DM patients compared with healthy control, the present results show that the genotypes and allele frequencies are significantly (p = 0.001). Conclusion: According to the Receiver operating characteristic (ROC) analysis, in the present results indicates E-Selectin is considered as a weak prognostic marker to distinguish T1DM patients. Additionally, no such correlation was found into the TLR-4 Asp299Gly (rs4986790) polymorphism in patients with T1D.